BMP‐2 Expression Correlates with Local Failure in Head and Neck Squamous Cell Carcinoma. (18th November 2013) - Sand, Jordan P.; Kokorina, Natalia A.; Zakharkin, Stanislav O.; Lewis, James S.; Nussenbaum, Brian
Abstract : Objective: Preclinical data show that exogenous administration of recombinant human bone morphogenetic protein‐2 (rhBMP‐2) to human oral carcinoma cell lines increases pathogenicity using a nude mouse model. The objectives of this study are to (1) describe the characteristics of baseline protein expression of BMP‐2 in head and neck squamous cell carcinomas (HNSCC) and (2) determine if BMP‐2 expression level correlates with worse oncologic outcomes. Study Design: Retrospective analysis of previously harvested patient samples. Setting: Academic medical center. Subjects: In total, 149 patients with oral cavity, oropharynx, larynx, and hypopharynx HNSCC treated between January 1, 1997, and December 31, 2004. Methods: A tissue microarray of HNSCC was assembled and immunohistochemistry for BMP‐2 performed. Staining was quantified using a standardized scoring system. Specimens were dichotomized into high or low expression level. Statistical analyses using log‐rank, Wilcoxon, and Fisher exact test were performed for associations between BMP‐2 protein level and clinicopathologic features and patient survival. Results: BMP‐2 expression at any level was noted in 146 of 149 (98%) of samples. Tumors with high BMP‐2 expression had higher rates of local failure compared with low‐expressing tumors (17.3% vs 6.3%; P =. 04). There was no significant association for BMP‐2 expression level with tumor location, T stage, N stage, overall survival, regional failure, or distant failure. Conclusion: Head and neck squamous cell carcinomas with high baseline BMP‐2 protein level are associated with higher rates of local recurrence. These data have important implications for using rhBMP‐2 in tissue engineering reconstructive approaches in the setting of cancer‐related defects.